The ASAS-SN catalogue of variable stars – V. Variables in the Southern hemisphere. Issue 1 (30th September 2019) - Jayasinghe, T; Stanek, K Z; Kochanek, C S; Shappee, B J; Holoien, T W-S; Thompson, T A; Prieto, J L; Dong, S; Pawlak, M; Pejcha, O; Shields, J V; Pojmanski, G; et al.
ABSTRACT: The All-Sky Automated Survey for Supernovae (ASAS-SN) provides long baseline (∼4 yr) light curves for sources brighter than V ≲ 17 mag across the whole sky. As part of our effort to characterize the variability of all the stellar sources visible in ASAS-SN, we have produced ∼30.1 million V -band light curves for sources in the Southern hemisphere using the APASS DR9 (AAVSO Photometric All-Sky Survey Data Release) catalogue as our input source list. We have systematically searched these sources for variability using a pipeline based on random forest classifiers. We have identified 220 000 variables, including 88 300 new discoveries. In particular, we have discovered 48 000 red pulsating variables, 23 000 eclipsing binaries, ∼2200 δ-Scuti variables, and 10 200 rotational variables. The light curves and characteristics of the variables are all available through the ASAS-SN variable stars data base (https://asas-sn.osu.edu/variables ). The pre-computed ASAS-SN V -band light curves for all the ∼30.1 million sources are available through the ASAS-SN photometry data base (https://asas-sn.osu.edu/photometry ). This effort will be extended to provide ASAS-SN light curves for sources in the Northern hemisphere and for V ≲ 17 mag sources across the whole sky that are not included in APASS DR9.